Комунікативні стратегії і тактики дискурсивної реалізації концепту СONSENSUS в англомовному публіцистичному дискурсі - Нісаноглу, Наталя Георгіївна; Нисаноглу, Наталья Георгиевна; Nisanoglu, Natalia (My University, 2020)
UK: Стаття присвячена визначенню комунікативних стратегій і тактик дискурсивної реалізації концепту СONSENSUS в англомовному публіцистичному дискурсі. З’ясовано, що використання певних комунікативних стратегій і тактик забезпечує здобуття прихильності адресата, досягнення згоди між мовцем і слухачем, взаєморозуміння як маркерів консен- сусу. На основі наведених прикладів визначено спроможність широкого спектру мовних засобів, які актуалізують концепт CONSENSUS, впливати на адресата з метою досягти успішності комунікації. EN: The paper focuses on revealing сommunicative strategies and tactics of the discursive realization of the concept CONSENSUS in English-language publicistic discourse. It has been established that using certain strategies and tactics provide an addressee’s garnering sympathy, achieving agreement between a speaker and a hearer, mutual understanding as the markers of consensus. The cited instances have exposed an ability of the variety of the lingual means, that actualize the concept CONSENSUS, to affect an addressee with a purpose to achieve successful communication.
Communicative Strategies and Tactics of the Discursive Realization of the Concept CONSENSUS in English-Language Publicistic Discourse
Keywords: комунікативні стратегії; комунікативні тактики; концепт СONSENSUS; дискурсивна реалізація; communicative strategies; communicative tactics; concept CONSENSUS; discursive realization